Alcohol attributed Oral Cancer and Oral microbiome: Emerging yet neglected research domain. (December 2021) - Yuwanati, Monal; Sarode, Sachin C.; Gadbail, Amol; Gondivkar, Shailesh; Sarode, Gargi S.
Highlights: Alcohol-attributed oral cancer should be assessed against a backdrop of oral microbes and poor oral hygiene. The oral microbiome in alcoholic can create acetaldehyde not only from the alcohol but also from the glucose; thus exposing the oral mucosa for longer periods and increasing the risk of oral cancer. Periodontal microorganism and alcohol can have symbiotic effect in oral cancers. Quality and quantity of alcohol consumed usually varies in low-middle income countries, which should be investigated to derive alcohol-attributed burden of oral cancer.